Le désir masculin en controverses - Camille Bajeux (Genre, Sexualité et Société)
This article analyzes two controversies that took place during the revision process of the Diagnostic and Statistical Manual of Mental Disorders (DSM) between 2008 and 2013. On this occasion, the working group on « paraphilia » – sexual attractions and behaviors that are deemed abnormal or pathological – proposed to include two new controversial mental disorders: the sexual attraction for rape (under the name of paraphilic coercive disorder) and the sexual attraction for pubescent teenagers (under the name of hebephilia). Drawing from the feminist critique of science as well as science and technology studies epistemologies, this research studies the production, shaping and negotiation of psychiatric knowledge on male sexuality during the revision process of the DSM. In so doing, it questions the boundaries between the normal and the pathological as well as the historical tensions and paradoxes at the core of the paraphilia section.